2013
DOI: 10.1017/s1755773913000246
|View full text |Cite
|
Sign up to set email alerts
|

Winners and losers of globalization in Europe: attitudes and ideologies

Abstract: Globalization pressures result in a new ideological conflict among Europeans. We use detailed items from the Eurobarometer survey on issues of immigration and European integration that measure the ideological perspective underpinning positions toward the EU. This provides a fine-grained analysis of the ideologies underlying the poles of the new globalization-centered conflict line, which we define as cosmopolitan and communitarian. Our results show that, next to socio-demographic characteristics, subjective me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
114
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(120 citation statements)
references
References 28 publications
1
114
0
5
Order By: Relevance
“…43, Heft 4, August 2014, S. 258-271 2 The unidimensionality of this set of identification variables among elites sharply contrasts with the bidimensionality of these identification variables among the general population. Various studies have indeed shown that supranational identification is independent of national identification among the general population (e. g., Hanquinet & Savage 2012;Pichler 2009a;Teney et al 2013). Our results shed light on a further potential elite-mass gap related to the relationships between national and supranational identifications.…”
supporting
confidence: 65%
See 3 more Smart Citations
“…43, Heft 4, August 2014, S. 258-271 2 The unidimensionality of this set of identification variables among elites sharply contrasts with the bidimensionality of these identification variables among the general population. Various studies have indeed shown that supranational identification is independent of national identification among the general population (e. g., Hanquinet & Savage 2012;Pichler 2009a;Teney et al 2013). Our results shed light on a further potential elite-mass gap related to the relationships between national and supranational identifications.…”
supporting
confidence: 65%
“…Our study can therefore push forward the debate on the rise of a new globalization cleavage: denationalization issues not only polarize public opinion into groups of losers and winners (Teney et al 2013) but also create a severe divide between the general population and elites. In line with the arguments of Schimmelfennig (2001) and Calhoun (2003), our results suggest that support for further opening up national borders can be considered part of the dominant ideology supported by the elites, who hold relatively uniform positive attitudes toward denationalization issues.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Scholars are aware of the role of citizen differences on aspects of the Globalist divide on political choice. Van der Brug and Van Spanje (2009) and Teney, Lacewell, and De Wilde (2014) argue that the Globalist-Nationalist cleavage is a second and emergent dimension of political conflict in Europe. Kriesi et al (2008) and Azmanova (2011) see the potential for the Globalist-Nationalist conflict to supplant the left-right economic cleavage in European politics.…”
mentioning
confidence: 99%